The Effect of Instruction on Learners' Pragmatic Awareness: a Focus on Refusals - Alcón Soler, Eva; Guzmán Pitarch, Josep (International Journal of English Studies, 2010)
The benefits of instruction on learners’ production and awareness of speech acts is well documented (see Alcón and Martínez-Flor, 2008, for a review of pragmatics in instructional contexts). However, few studies examine the influence that instruction may have on the cognitive processes involved in speech act production (Félix- Brasdefer, 2008). In order to address this research gap, and taking into account the discussion in research on the concept of attention and related terms such as awareness (see Al-Hejin, 2004, for a review of the role of attention and awareness in second language acquisition research) this paper reports on the benefits of instruction on learners’ attention and awareness during the performance of refusals. Thus, based on a pedagogical proposal for teaching refusals at the discourse level, we focus on the benefits that this pedagogical proposal can have on the information attended to during the planning and execution of refusals. Secondly, we explore whether instruction makes a difference in learners’ awareness of refusals.